Portraying Orang Ulu’s Culture in Belaga, Sarawak Through Participatory Art (Interactive – Video Mapping – Sound Visualization) - Anuar, Ayob; Hasnizam, Abdul Wahid; Wan Jamarul Imran, Wan Abdullah Thani
This research is designed to invite selected participants from community resided Belaga that is Orang Ulu ethnic; to participate, collaborate and engage interactively both through visual and sound in portraying their vanishing culture (tekna - traditional oral presentation, tattoo, sape, and ngajat dance) to be shared with public around Malaysia. It will also be an inclusive platform for them at large to share their unique culture and lifestyle which is hardly to be seen nowadays.